The influence of salt solution as curing media towards curing time and compressive strength of heat cured acrylic resin - Stephanie Yessica Hartanto; Kartika Andari Wulan; Delvi Fitriani; Lisda Damayanti; An-Nissa Kusumadewi (Indonesia Prosthodontic Association, 2023)
Heat-cured acrylic resin is commonly used as denture base materials. The time needed for its polymerization makes the process less efficient. The salt solution has a higher boiling point and more stable molecular bonding, which is expected to shorten the curing time of HCAR. This article determines the influence of salt solution as curing media on curing time and compressive strength of HCAR. This experimental laboratory study used 25 samples of HCAR with 25.4x12.7x12.7 mm by dimension. Samples were boiled in water at 74oC for 120 minutes as a control, in 35% salt solution at 74oC for 30, 60, 90, and 120 minutes as treatment groups, and then all groups were boiled at 100oC for 60 minutes. The compressive strength of each sample was tested using an Autograph AG-10TE. The highest com-pressive strength and fastest setting time were shown in samples boiled in a salt solution for 60 minutes. One-way Anova followed by a post hoc Tukey-HSD test showed no significant compressive strength differences in each group (p>0.05). It is concluded that salt solution usage as curing media fastens the curing time and results in the same compressive strength within all groups.